The Pore-Forming Subunit C2IIa of the Binary Clostridium botulinum C2 Toxin Reduces the Chemotactic Translocation of Human Polymorphonuclear Leukocytes - Eisele, Julia; Schreiner, Simone; Borho, Joscha; Fischer, Stephan; Heber, Sebastian; Endres, Sascha; Fellermann, Maximilian; Wohlgemuth, Lisa; Huber-Lang, Markus; Fois, Giorgio; Fauler, Michael; Frick, Manfred; et al. (Frontiers in Pharmacology, 2022)
The binary C2 toxin of Clostridium (C.) botulinum consists of two non-linked proteins, the enzyme subunit C2I and the separate binding/transport subunit C2II. To exhibit toxic effects on mammalian cells, proteolytically activated C2II (C2IIa) forms barrel-shaped heptamers that bind to carbohydrate receptors which are present on all mammalian cell types. C2I binds to C2IIa and the toxin complexes are internalized via receptor-mediated endocytosis. In acidified endosomal vesicles, C2IIa heptamers change their conformation and insert as pores into endosomal membranes. These pores serve as translocation-channels for the subsequent transport of C2I from the endosomal lumen into the cytosol. There, C2I mono-ADP-ribosylates G-actin, which results in depolymerization of F-actin and cell rounding. Noteworthy, so far morphological changes in cells were only observed after incubation with the complete C2 toxin, i.e. C2IIa plus C2I, but not with the single subunits. Unexpectedly, we observed that the non-catalytic transport subunit C2IIa (but not C2II) alone induced morphological changes and actin alterations in primary human polymorphonuclear leukocytes (PMNs, alias neutrophils) from healthy donors ex vivo, but not macrophages, epithelial and endothelial cells, as detected by phase contrast microscopy and fluorescent microscopy of the actin cytoskeleton. This suggests a PMN selective mode of action for C2IIa. The cytotoxicity of C2IIa on PMNs was prevented by C2IIa pore blockers and treatment with C2IIa (but not C2II) rapidly induced Ca2+ influx in PMNs, suggesting that pore-formation by C2IIa in cell membranes of PMNs is crucial for this effect. In addition, incubation of primary human PMNs with C2IIa decreased their chemotaxis ex vivo through porous culture inserts and in co-culture with human endothelial cells which is closer to the physiological extravasation process. In conclusion, the results suggest that C2IIa is a PMN-selective inhibitor of chemotaxis. This provides new knowledge for a pathophysiological role of C2 toxin as a modulator of innate immune cells and makes C2IIa an attractive candidate for the development of novel pharmacological strategies to selectively down-modulate the excessive and detrimental PMN recruitment into organs after traumatic injuries.